ATIM-05. A PHASE I STUDY TARGETING NEWLY DIAGNOSED GLIOBLASTOMA WITH ANTI-CD3 × ANTI-EGFR BISPECIFIC ANTIBODY ARMED T CELLS (EGFR BATS) IN COMBINATION WITH RADIATION AND TEMOZOLOMIDE. (11th November 2019) - Fadul, Camilo; Kim, Jungeun; Thakur, Archana; Purow, Benjamin; Lopes, Maria-Beatriz; Schiff, David; Kassay-McAllister, Jessica; Donahue, Joseph; Liu, Qin; Lum, Lawrence
Abstract: Overcoming the highly immunosuppressive glioblastoma (GBM) microenvironment is critical to successful immunotherapy. In a recently-launched phase I trial we are examining the safety and feasibility of a novel adoptive cell immunotherapy platform, activated T cells (ATC) with anti-CD3 X anti-EGFR bispecific antibody (EGFR BATs), for patients with newly-diagnosed GBM. Autologous T cells obtained before radiation and chemotherapy are expanded and activated, becoming cytotoxic T lymphocytes. We postulate that these activated T cells armed with bispecific antibody will enhance the response to radiation/temozolomide and potentially increase trafficking to the GBM microenvironment. In a 3 + 3 design dose-escalation trial, we will determine the maximum tolerated dose (MTD) of three dose tiers of EGFR BATs (80, 120 and 160 billion cells divided in eight infusions) in combination with radiation/temozolomide in patients with newly-diagnosed GBM. Patients undergo leukapheresis prior to initiating radiation/temozolomide. Patients receive EGFR BATs on days 14 and 21 after finishing concurrent RT/ temozolomide and on day 21 of six cycles of adjuvant temozolomide. We are measuring peripheral blood immune response before and after immunotherapy and correlating the results with patient characteristics and clinical outcomes. The first four patients have been treated at the first dose tier (80 billion cells) without any dose-limiting toxicity. Updated safety and feasibility results on the patients in the first two dose tiers will be presented, as well as immune monitoring studies, imaging studies, and clinical outcomes.